2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090370
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented toys for studying power and precision grasp forces in infants

Abstract: Currently the study of infants grasping development is purely clinical, based on functional scales or on the observation of the infant while playing; no quantitative variables are measured or known for diagnosis of eventually disturbed development. The aim of this work is to show the results of a longitudinal study achieved by using a "baby gym" composed by a set of instrumented toys, as a tool to measure and stimulate grasping actions, in infants from 4 to 9 months of life. The study has been carried out with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Additional efforts are needed to extend kinematic and kinetic analysis to musculoskeletal injuries (e.g., osteoarthritis, carpal tunnel syndrome, rheumatoid arthritis, stenosing tenosynovitis), often causative of complex hand disability [ 3 ]. The exploitation of new technologies-aided hand functional assessment methods in the context of neurodegenerative [ 53 , 54 ] and neurodevelopment disorders [ 43 , 55 ] could provide interesting results. As an example, technologies able to track kinematic information about fine hand use in free-living conditions could support early detection of fine motor impairments in neurodegenerative disorders [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional efforts are needed to extend kinematic and kinetic analysis to musculoskeletal injuries (e.g., osteoarthritis, carpal tunnel syndrome, rheumatoid arthritis, stenosing tenosynovitis), often causative of complex hand disability [ 3 ]. The exploitation of new technologies-aided hand functional assessment methods in the context of neurodegenerative [ 53 , 54 ] and neurodevelopment disorders [ 43 , 55 ] could provide interesting results. As an example, technologies able to track kinematic information about fine hand use in free-living conditions could support early detection of fine motor impairments in neurodegenerative disorders [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, another direction consists of instrumenting toys with sensors, enabling assessment as well as a game-like interface, similar to rehabilitation robots (though without the capability to move a child’s limbs). Early studies summarized in Table 1 have created such “intelligent toys” from familiar toys equipped with light-weight sensors ( 28 31 ), that encourage play through goal-orientated activity with regular positive feedback ( 29 , 32 35 ). In general, these studies have demonstrated only the feasibility of intelligent toys to derive quantitative movement measures in healthy young infants.…”
Section: Early Infant Motor Development and Assessmentmentioning
confidence: 99%
“…An instrumented sorting block toy was shown to be sufficiently sensitive to demonstrate differences in performance related to motor planning and task difficulty ( 31 ). This concept has also been extended further for babies by integrating intelligent toys into a baby gym, providing an engaging and involving enriched environment for an ecological assessment of reaching patterns and grasping forces in infants aged between 4 and 9 months ( 32 , 34 , 35 ). Longitudinal trials have demonstrated that this system is capable of providing quantitative measures of power grip maturation patterns in healthy infant subjects, and has the potential to be employed to objectively assess hand function in this naturally uncooperative population ( 34 , 36 ).…”
Section: Early Infant Motor Development and Assessmentmentioning
confidence: 99%
“…For the past near-decade, the greater part of infant neuromotor sensing technology research has focused on detecting and analyzing patterns of movement, measuring, and modeling the same phenomena as the GMA. 16 , 17 , 18 , 19 , 20 , 21 , 22 The CareToy EU Project that produced an “intelligent baby gym” for home use with infants at risk for neurodevelopmental disorders is the most extensive example of this line of research and development. 18 , 19 , 23 , 24 …”
mentioning
confidence: 99%
“…These forces are measured through sensors embedded in toys designed to be visually attractive to infants and shaped to fit easily within their hands. 16 , 17 , 18 , 19 , 20 , 21 , 22 The CareToy uses sensorized toys for measuring grip force as part of a home-based baby gym for treatment and assessment of infants at risk of delay. 23 Sgandurra et al used CareToy to examine typically developing infants with sensorized toys from 18-41 weeks and found an increase in power grip force between 18 and 30 weeks of age followed by a plateau period.…”
mentioning
confidence: 99%